The impact of burnout and occupational stress on sexual function in both male and female individuals: a cross-sectional study - Papaefstathiou, Efstathios; Apostolopoulou, Aikaterini; Papaefstathiou, Eirini; Moysidis, Kyriakos; Hatzimouratidis, Konstantinos; Sarafis, Pavlos (My University, 2020)
Burnout and occupational stress are common problems in the modern society. The aim of the study was to investigate the association of burnout and occupational stress with sexual dysfunction. The study enrolled 251 residents, 143 males and 108 females. The personal medical history, demographics, and professional data of the participants were recorded. The Copenhagen Burnout Inventory (CBI) and the job stress measure were used for the evaluation of burnout and occupational stress, correspondingly. The International Index of Erectile Function (IIEF) and the Female Sexual Function Index (FSFI) were used for the assessment of sexual function. The majority of the respondents were males (57%), with a mean age of 31 years. From the analysis concerning males, personal burnout, hypertension, and alcohol consumption correlated independently with erectile dysfunction (p = 0.001) and reduced total satisfaction (p < 0.001). With respect to the female participants, the number of children was found to be related to easier arousal (p = 0.009), better lubrication (p = 0.006), and orgasm (p = 0.016). Contrariwise, job stress related negatively with lubrication (p = 0.031) and orgasm (p = 0.012). This is the first study examining the effect of burnout on sexual function. Personal burnout was observed to be associated with sexual dysfunction in men whereas job stress correlated with female sexual problems. Further examination in different occupational groups and a greater number of patients is required.
Keywords: Infertility; Women; Infertility-related stress